Congenital adnexal cyst in a newborn: diagnostic dilemma - A., Thumjaa; Maru, Sindhu; Reddy K., Vamsi Krishna; R., Rajaselvan (International Journal of Contemporary Pediatrics, 2016)
Cystic lesions are rare perinatal, diagnosed intra-abdominal mass. Complications may occur during the vaginal delivery because of such mass in abdomen. Even it is difficult to make a diagnosis on routine clinical examination. Management of both ovarian and mesenteric cyst is surgical removal.